THE ROLE OF ENTREPRENEURSHIP IN COMBATING POVERTY - Fozilov Vahobjon Akrom o’g’li (TADQIQOTLAR, 2026)
Annotation. This article examines the role of entrepreneurship in combating poverty and promoting sustainable economic development. The study analyzes how entrepreneurial  activity  contributes  to  employment  generation,  income  growth, innovation, and improvement of living standards. Special attention is given to small and  medium-sized  enterprises,  digital  entrepreneurship,  financial  inclusion,  and government support mechanisms. The article also evaluates the relationship between entrepreneurship development and poverty reduction using statistical and comparative analysis.